Modeling and Simulation in Plane Geometry of Dirt Deposit in Heat Exchangers by Deposit of Ice in varying system - QUENUM, ALPHONSE CODJO; KOSSOU, CODJO TOUSSAINT; ASSOUDO, ABDOULAYE; AHOUANNOU, CLÉMENT; SANYA, EMILE ADJIBADÉ; MEZRHAB, Ahmed; FEIDT, Michel (My University, 2013)
This article is devoted to modeling the mechanism of fouling in heat exchangers plates unsteady. The used simulation is based on the monitoring of the evolution of the ice at the changing phase (solidification) in water flowing in a rectangular section pipe, externally cooled. Cooling is done so that the heat exchange coefficient is uniform between coolant in a turbulent flow and the wall. The problem, numerically solved by finite difference method, provided results that allowed the exploration of the effects of the most relevant parameters such as the coefficient overheated liquid, Biotand Reynolds numbers, the axial position, the cooling mode and temperature, the evolution of the ice layer simulating the deposit of dirt.
Keywords: Exchanger; Plates; Dirt; Simulation; Coefficient of overheating